2015
DOI: 10.1175/jhm-d-14-0106.1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Seasonality over the Indian Subcontinent: An Evaluation of Gauge, Reanalyses, and Satellite Retrievals

Abstract: This paper evaluates the seasonal (winter, premonsoon, monsoon, and postmonsoon) performance of seven precipitation products from three different sources: gridded station data, satellite-derived data, and reanalyses products over the Indian subcontinent for a period of 10 years (1997/98-2006/07). The evaluated precipitation products are the Asian Precipitation-Highly-Resolved Observational Data Integration Towards Evaluation of the Water Resources (APHRODITE), the Climate Prediction Center unified (CPC-uni), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 69 publications
5
84
0
Order By: Relevance
“…CPC-UNI exhibites lowest precipitation over Myanmar and the neighboring regions. This is similar to the findings of Rana et al (2015), who showed that CPC-UNI poorly simulates seasonal mean precipitation over the same region. ERA-Interim also tends to show lower values over India and the maritime continent.…”
Section: Climatological Features Over the Asian Domainsupporting
confidence: 91%
See 3 more Smart Citations
“…CPC-UNI exhibites lowest precipitation over Myanmar and the neighboring regions. This is similar to the findings of Rana et al (2015), who showed that CPC-UNI poorly simulates seasonal mean precipitation over the same region. ERA-Interim also tends to show lower values over India and the maritime continent.…”
Section: Climatological Features Over the Asian Domainsupporting
confidence: 91%
“…Figure 9 shows the decadal trends of extreme rainfall (i.e., 95th percentile precipitation for JJA) in the datasets over the period 1998-2007 calculated through a linear regression coefficient. Except for APHRODITE, ERA-Interim, and JRA55, the rest shows a remarkable increasing trend over central India, which is consistent with the finding of Rana et al (2015) and Prakash et al (2014). Singh et al (2013) found that APHRODITE has opposite trend signs for extreme precipitation intensity from the 2000s onwards when compared with the IMD dataset (2140 rain-gauge station).…”
Section: Interannual Variabilitysupporting
confidence: 81%
See 2 more Smart Citations
“…These findings also suggest that satellite algorithm estimations from TMPA 3B42 v7 are suitable for low to medium ground elevations (>40 MASL) during extreme rainfalls. This proves that TMPA 3B42 v7 estimations have better agreement with gauging observations for higher ground levels than lower levels, which matches with other's study findings [27][28][29]. Generally, overall results indicate the tendency for underestimations by TMPA 3B42 v7 when compared to rain gauge observations during seasonal heavy precipitation, regardless of varying elevations.…”
Section: Performance Assessment Using Continuous Statisticssupporting
confidence: 87%